Attrition of Ca‐based CO2‐adsorbents by a high velocity gas jet. Issue 4 (7th September 2012) - Valverde, Jose Manuel; Quintanilla, Miguel Angel Sanchez
<x xml:space="preserve">Abstract</x> Attrition of Ca‐based adsorbents is a subject of interest that determines the efficiency of the Ca‐looping process for CO2 capture. In this article, we report an experimental test to assess the mechanical strength of cohesive Ca‐based adsorbents based on particle sizing by laser diffractometry. In this technique, the powder sample is dispersed, either by a high velocity air jet (dry dispersion) or by a liquid before the particle size distribution (PSD) is measured. In the dry dispersion unit, particle aggregates are subjected to high energy collisions intended to cause their fragmentation. The PSDs obtained at a low dispersive air pressure for calcined CaO shows that there is a remarkable population of large aggregates due to strong van der Waals of attraction. A second population consists of compact small aggregates, which are relatively stronger due to material sintering at interparticle contacts. As the dispersive air pressure is increased, these aggregates are broken. Their size scales as a power law of the jet air velocity in agreement with the prediction of a fracture mechanics theory of brittle materials. In contrast, the population of large aggregates of a modified adsorbent, consisting of a CaO/nano‐silica composite, is not significative, which can be attributed to the effect of nano‐silica in decreasing the van der Waals attractive force. Moreover, the small compact aggregates of the composite are broken at a lower rate with the dispersive air pressure. The enhanced strength of these composite aggregates is further supported by the PSDs obtained for samples dispersed in a liquid and previously excited by high energy ultrasonication. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1096–1107, 2013